Analisis Pengaruh Sistem Pembayaran Non Tunai Terhadap Pertumbuhan Ekonomi Indonesia Periode Tahun 2013-2023 - Fina Kartika Sari; Ghofur, Muhammad Abdul (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2025)
This study focuses on analyzing the effect of the use of non-cash payment systems on Indonesia's economic growth. The data used in this study are secondary data in the form of quarterly time series with the period 2013-2023. The method used is quantitative with data collection techniques through literature study and multiple linear regression analysis techniques with Ordinary Least Square (OLS). The results showed that non-cash transactions using credit cards, debit cards/ATMs, and m-banking had a positive and significant effect on economic growth. The effect is shown partially and simultaneously.